2023
DOI: 10.1111/ddg.15180
|View full text |Cite
|
Sign up to set email alerts
|

Applying an artificial intelligence deep learning approach to routine dermatopathological diagnosis of basal cell carcinoma

Nicole Duschner,
Daniel Otero Baguer,
Maximilian Schmidt
et al.

Abstract: SummaryBackgroundInstitutes of dermatopathology are faced with considerable challenges including a continuously rising numbers of submitted specimens and a shortage of specialized health care practitioners. Basal cell carcinoma (BCC) is one of the most common tumors in the fair‐skinned western population and represents a major part of samples submitted for histological evaluation. Digitalizing glass slides has enabled the application of artificial intelligence (AI)‐based procedures. To date, these methods have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
1
0
2
Order By: Relevance
“…Duschner et al applied AI to automated diagnosis of BCCs, and demonstrated both sensitivity and specificity of over 98%. Notably, the model demonstrated successful generalization to samples from other centers with similar sensitivity and specificity ( 54 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Duschner et al applied AI to automated diagnosis of BCCs, and demonstrated both sensitivity and specificity of over 98%. Notably, the model demonstrated successful generalization to samples from other centers with similar sensitivity and specificity ( 54 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Eine gute Übersicht über diese Studien findet sich in der Arbeit von Duschner et al. in dieser Ausgabe 6 . Eine wichtige Limitierung dieser PoC‐Studien ist allerdings, dass sie meist monozentrisch erfolgten und die Genauigkeit des Modells anhand eines Testdatensatzes errechnet wird, der zuvor vom Gesamtdatensatz separiert wurde.…”
unclassified
“…wurde die Genauigkeit eines zuvor in einer PoC‐Studie trainierten Modells, erstmalig an einem nicht‐selektierten Datensatz aus der Routinediagnostik untersucht. Das KI‐System erzielte dabei eine hohe Sensitivität von 98.23 % und eine Spezifität von 98.51 %, vergleichbar mit den Werten aus der PoC‐Studie 6,7 . Besonders erwähnenswert ist, dass das Modell ohne weiteres Training eine ähnliche Genauigkeit bei der Analyse von WSI aus zwei anderen Laboren erzielte.…”
unclassified